Efectos de cuatro niveles dietéticos de harina de semilla de chocho (Lupinus mutabilis) sobre parámetros productivos, desarrollo intestinal y valores hematológicos en pavos de ocho semanas - Paredes A., Manuel (2020)
The effect of four dietary levels of lupine seed meal (Lupinus mutabilis, HCH) on growth performance, intestinal tract development and haematological values ​​were evaluated in male turkeys of the one-day BUT line. The turkeys were distributed in four groups with different diets for 56 days: L0 (control) diet without HCH, and L30, L60 and L90 diets containing 30, 60 and 90 g/kg of HCH, respectively. Increased levels of HCH inclusion in the diet, added at the expense of soybean meal, contributed to an increase in fibre concentrations in the experimental diets. Daily feed intake decreased in HCH treatments and feed conversion and bodyweight gain of birds were affected in treatments of 60 and 90 g / kg of HCH inclusion (p<0.05). High dietary levels of HCH led to an increase (p<0.01) of the digesta in the ileum and in the cecum, an increase in the relative tissue mass (p<0.01), as well as a decrease in pH values of the digesta (p<0.01). The increase in HCH in the diet did not alter the haematological values. It is concluded that HCH can be considered as a safe and effective alternative for dietary inclusion at levels of 30 g/kg in starting diets for young turkeys.